Beyond the Biological Effect of a Chemically Characterized Poplar Propolis: Antibacterial and Antiviral Activity and Comparison with Flurbiprofen in Cytokines Release by LPS-Stimulated Human Mononuclear Cells - Governa, Paolo; Cusi, Maria Grazia; Borgonetti, Vittoria; Sforcin, Jose Mauricio [UNESP]; Terrosi, Chiara; Baini, Giulia; Miraldi, Elisabetta; Biagi, Marco (Mdpi, 2019)
Bee propolis, especially Euro-Asian poplar propolis, is among the most well-known natural products traditionally used to treat pharyngitis and minor wounds. The aim of this research was to investigate the pharmacological properties responsible for poplar propolis effectiveness using, for the first time, different in vitro approaches applied to a chemically characterized sample. The anti-inflammatory activity was compared with flurbiprofen by determining pro-inflammatory cytokines released by lipopolysaccharide-stimulated human peripheral blood mononuclear cells (PBMC). The antibacterial activity against Gram+ and Gram- bacteria was assessed, as well as antiviral effects on H1N1 influenza a virus. Poplar propolis (5 and 25 mu g/mL) exerted a concentration-dependent anti-inflammatory activity. In this range of concentrations, propolis effect was not inferior to flurbiprofen on cytokines released by lipopolysaccharide (LPS)-stimulated human PBMC. Poplar propolis was found to upregulate IL-6 and IL-1 beta in non-stimulated PBMC. S. aureus, S. pyogenes, and S. pneumoniae were the most susceptible bacterial strains with inhibitory concentrations ranging from 156 to 625 mu g/mL. A direct anti-influenza activity was not clearly seen. Effective anti-inflammatory concentrations of propolis were significantly lower than the antibacterial and antiviral ones and results suggested that the anti-inflammatory activity was the most important feature of poplar propolis linked to its rationale use in medicine.
Keywords: poplar propolis; anti-inflammatory; cytokines release; flurbiprofen; flavonoids; antibacterial; influenza virus; neuraminidase